The Handbook of Economic Sociology : Second Edition - Swedberg, Richard; Smelser, Neil J. (Book collections on Project MUSE., 2005)
Reflecting the growing interest in economic sociology, this new edition has been comprehensively updated to include important developments in this field of scholarship since the mid-nineties.